Melatonin: a multifaceted regulator of plant growth and versatile modulator of biotic and abiotic stress response - Shaziya Sultana,; Sharmistha Barthakur, (Annals of Agricultural Research, 2024)
Melatonin earlier exclusively recognised for its role as a neurohormone in animals, has emerged as a potent signalling molecule in the plant kingdom in recent times. Extensive research conducted in the past decade has unveiled its intriguing involvement in various aspects of plant growth and stress tolerance. This review provides an overview of the diverse functions of melatonin in plant growth, development and its involve ment in mitigating biotic and abiotic stressors. Melatonin exhibits antimicrobial properties, aiding plants in defence against various diseases by activating the signalling cascade of jasmonic acid and salicylic acid pathway. It acts as a potent antioxidant by scavenging reactive oxygen species, mitigates the oxidative dam age and cellular injury caused by various stressors. Its diverse functions as a hormone and signalling mol ecule make it a promising target for enhancing crop productivity and stress resilience. However, further mechanistic understanding is needed to fully understand the intricate mechanisms underlying melatonin’s action in plants, which may open new avenues for innovative agricultural practices in the future.